Axe Production and Exchange in the Seine Valley (France) - François Giligny (Internet Archaeology, 2009)
The particular aim of this article is to examine territories and the role of lithic raw material extraction and production sites in the Seine basin during the Neolithic. While producer sites are indeed central to the diffusion process, they are not necessarily located in the geographical centre of a territory, and their distribution should be analysed in relation to other sites such as settlements, burials and places of communal assembly. The evidence from several categories of monument is considered in relation to the mapped distribution of over 3000 axes, some of them originating in the Armorican Massif and the Alps. The resultant patterns suggest that the Seine valley was a circulation and exchange route, serving as a geographical interchange for the diffusion of Armorican and Alpine axes.